Assessing the effect of On-site supportive communication training (On-site SCT) on doctor burnout: a randomized controlled trial - K.K. Antonsen; J.D. Lyhne; A.T. Johnsen; S. Eßer-Naumann; L.Ø. Poulsen; L. Lund; S. Timm; L.H. Jensen (BMC Medical Education)
Abstract Background Burnout is a critical factor that can influence the quality of care that doctors provide to their patients. Previous research suggests a link between inadequate communication skills training and burnout, and various approaches to enhance communication skills have been explored as a means to address this issue. However, evidence of the effect of these approaches is lacking. The aim of this study is to assess the effect of the novel On-site Supportive Communication Training (On-site SCT) in enhancing communication skills among oncologists and thereby addressing burnout. Methods This randomized, controlled, multicenter study was conducted across three oncological departments in Denmark. Doctors were eligible if they worked in the outpatient clinic at least four days per month and provided informed consent. Doctors in the intervention group underwent a two-hour introduction followed by three full days of On-site SCT facilitated by in-house psychologists, while those in the control group continued standard practices. Pre- and post-intervention assessments on burnout (Copenhagen Burnout Inventory) were conducted, as were assessments of related constructs (job satisfaction and communication self-efficacy). Differences in pre- and post- assessments were analyzed using a paired t-test. Feasibility was assessed descriptively by comparing intervention days with planned schedule, and doctors’ satisfaction with the intervention was assessed systematically by questionnaire. Results Of 101 screened doctors, 89 (88%) consented and were randomized. 65% were female, and the mean age was 46 (range 27 to 75). Due to nine exclusions, data from 39 doctors in the intervention group and 41 doctors in the control group were available for analysis. At baseline, doctors exhibited lower levels of burnout than reported in international literature. No statistically significant improvements in burnout (p > 0.05) were demonstrated post-intervention. Despite non-significant changes, the doctors reported an improvement in communication self-efficacy. The program showed high feasibility and received positive feedback from participating doctors. Conclusions Our findings caution against assuming a causal relationship between short-term interventions and a complex phenomenon like burnout. On-site SCT demonstrated high feasibility, participation rate and acceptance. This underscores its potential value in clinical settings. Consequently, On-site SCT will be implemented at the Department of Oncology, Vejle University Hospital, to facilitate further refinement based on ongoing feedback and to explore long-term outcomes. Trial registration December 2022– The Region of Southern Denmark (22/57137). April 2023– ClinicalTrials.gov (NCT05842083). April 2023– The Research Ethics Committee at the University of Southern Denmark (23/19397).